Staged organosolv pretreatment to increase net energy and reactive lignin yield in whole oil palm tree biorefinery. (April 2021) - Islam, Md Khairul; Thaemngoen, Amornpan; Lau, Chun Yin; Guan, Jianyu; Yeung, Chi Shun; Chaiprapat, Sumate; Leu, Shao-Yuan
Graphical abstract: Highlights: Values and insights of novel staged organosolv fractionation were elucidated; 1.21 giga joules (GJ)/ton-biomass more energy than the single stage process; Condensed lignin reduced from 21.7% to under detection limit under 2D HSQC NMR; 142.25 tonnes of bioethanol can be produced from palm biomass per each hectare; Empty fruit bunch showed the highest potential than trunk, frond, and leaves; Abstract: Pretreatment is the most crucial and energy-intensive unit process affecting the feasibility of biorefinery, especially when lignin valorization is of concern. This study investigated and quantified the potential benefits of an innovative staged organosolv (OS)-dilute acid (DA) pretreatment process for whole oil palm tree residues conversion. The staged OS-DA pretreatment resulted in approximately five times higher net energy (1.50 GJ/tonne) over the single-step OSDA process (0.30GJ/tonne) due to potential energy saving on solvent recovery and less water consumption. For sugar, OS-DA pretreated substrate achieved more than 90% of cellulose digestibility which was more than 40% higher than DA-OS substrate. For mono-lignin, significant reduction in crude lignin condensation (21.7%) was confirmed by two-dimensional NMR analysis. The overall mass balance showed that approximately 142.45 tonnes of bioethanol, or a net energy yield of 969.5 GJ, can be produced by OS-DA process from palm tree residues per hectare of oil palm farm.